Long-Term Survival after Salvage Surgery for Local Failure after Definitive Chemoradiation Therapy for Locally Advanced Non-small Cell Lung Cancer - Schreiner, Waldemar; Dudek, Wojciech; Lettmaier, Sebastian; Fietkau, Rainer; Sirbu, Horia (The Thoracic and Cardiovascular Surgeon, 2018)
Background The incidence of local failure and residual tumor after definitive chemoradiation therapy (dCRT) for locally advanced non-small-cell lung cancer remains high, irrespective of applied radiation dose (>59 Gy). So-called salvage surgery has been suggested as a feasible treatment option after failure of definitive chemoradiation for locally advanced non-small cell lung cancer (NSCLC). Experience with salvage lung surgery (SLS) is limited, and long-term survival is rarely reported. Patient selection criteria for surgical lung salvage are not defined. The aim of this study was to assess postoperative survival and perioperative morbidity/mortality to identify prognostic factors and to define patient selection criteria.Patients and Methods Records of 13 consecutive patients with locally advanced NSCLC, who underwent SLS at a single institution between March 2011 and November 2016, were reviewed. Descriptive statistics were applied for patient characteristics and surgical and oncological outcome. Survival rates were calculated using the Kaplan–Meier method and were compared with the long-rank test.Results All patients initially received curative-intent definitive chemoradiation with median radiation doses of 66 Gy (range 59.4–72) and concurrent platinum-based chemotherapy. Clinical tumor stage before definitive chemoradiation was IIIA in 9, IIIB in 3, IV in 1 patients. Median interval between definitive chemoradiation and salvage surgery was 6.7 months. Perioperative morbidity and 30-days-mortality was 38% and 7.7%, respectively. The median postoperative survival and estimated 5-year survival rate were 29.7 months and 46%, respectively.Conclusion SLS in patients with locally advanced non-small cell lung surgery following dCRT is feasible, prolongs long-term survival and allows local tumor control. Selection criteria remain undefined and patients should be considered surgical candidates during multidisciplinary team conference.
Keywords: salvage surgery lung cancer; definitive chemoradiation therapy; local failure